Code-Mixing and Code-Switching in Cameroon Social Media - Tabe, Camilla Arundie (International Journal of Linguistics and Translation Studies, 2023)
This study examines code-mixing and code-switching in Cameroon social media to find out the languages that are mixed or switched to and the reasons for the phenomenon. Insights came from the structural approach to code-switching, which measures the degree to which an L2 is incorporated into an L1 or vice versa (Poplack, 1980, 2000; Poplack & Meechan, 1995; Myers-Scotton, 1993b, 2002). Data comprises 245 e-messages which were drawn from e-mail(s) (100), Facebook (60) and WhatsApp (85). The data were collected through screenshots with the use of android phones. Quantitative and qualitative analyses of data show the presence of code-mixing and code-switching from English to French (48%), English to Cameroon Pidgin English (18.4%) and English to home languages (11.5%). It was construed that Cameroons mix or switch codes because of their multicultural and multilingual backgrounds.